Generalities. Boarding routes. Exploration. Excision time: Roundtable on Surgical Technique Total gastrectomy: coordinator Juan E Cendán Alfonzo - Cendán Alfonzo, Juan E; Delgado, Bolívar; Mérola, Lorenzo (Cirugía del Uruguay, 1974)
Total gastrectomy is undoubtedly the most complex operation of gastric surgery, not so much because of the number of conditions in which it is indicated, but because of the variety of proceduresTotal gastrectomy is undoubtedly the most complex operation of gastric surgery, not so much because of the number of conditions in which it is indicated, but because of the variety of proceduresand applicable techniques, both in the time of excision and in the restoration of the digestive transit.